Psychometry Characteristic of Standard Progressive Matrices (SPM) - Annisa Suci Rahmadani; Widyastuti, Widyastuti; Asri, Asmulyani (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
The purpose of this research is to analyze the psychometric characteristics of Standard Progressive Matrices (SPM), that is analysis of item difficulty index, item discrimination index, distractor effectiveness, construct reliability, and construct validity. The approach used in the study is quantitative approach. The population of the study was junior and senior high school students and the sample of the study was 1.547 junior high school students and 1.528 senior high school students. The results of the item difficulty index analysis on SPM are not in accordance with the order of difficulty level items. The results of the discrimination index analysis on SPM shows that there are 39 to 41 items with excellent categories. The results of the analysis of the effectiveness of the distractors on SPM shows that there are 42 to 45 items that had effective distracters. The overall results of the analysis of the construct reliability on the SPM are reliable and can be trusted as a test tool. The results of the analysis of the construct validity of each item show that there are 47 to 48 valid items on SPM. The overall analysis shows that SPM is able to perform the measuring function properly.